Oxygen Stripping in Deaerator Feed Water: Condensation on Spray Droplets - K. V., Sharma; K. V., Suryanarayana; P. K., Sarma; V., Dharma Rao; T., Subramanyam (Springer-Verlag, 2010)
Deaerator is used to remove oxygen from boiler feed-water. Experiments with deaerator indicate that the droplet diameter decreases with increasing the mass flow rate of water and the increasing deaerator pressure leads to increase in heat and mass transfer coefficients. The mass transfer coefficients are found to increase with increasing the deaerator pressure, the independent of length and the oxygen concentration in inlet water.